On the Axiomatisation of Elgesem's Logic of Agency and Ability. - Governatori, Guido; Rotolo, Antonino (Journal of Philosophical Logic, 2005)
In this paper we show that the Hilbert system of agency and ability presented by Dag Elgesem is incomplete with respect to the intended semantics. We argue that completeness result may be easily regained. Finally, we shortly discuss some issues related to the philosophical intuition behind his approach. This is done by examining Elgesem's modal logic of agency and ability using semantics with different flavours.